Effect of Temperature on Cu-doped p-ZnTe Thin-Films (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In this paper we study the effect of temperature in 150 (±5) and 80 (±5) nm p-ZnTe thin- films immersed in 60 mgCu(NO3)2-3H2O/150 ml (H2O) for 1 minute, and heated at 200 and 300 °C for 30 minutes. Active layers were deposited by pulsed-laser deposition (PLD) at room temperature. Electrical parameters in un-doped films were around 108  ?109 ? and these values decreased to ~ 103 ? when the films were immersed in a Cu solution. The Cu-doped samples heated at 300 °C showed a completely homogeneous doping. X-ray diffraction (XRD) patterns showed the orthorhombic structure at 200 and 300 °C.